Pembinaan Kesadaran Digital: Mencegah dampak Buruk Media Sosial dan Etika Penggunaannya pada Santri Pondok Pesantren Pantura Pamekasan - Yanto, Yanto; Anwari, Moh.; Rofiki, Rofiki (Civiliza Publishing, 2024)
It is important to understand that social media provides very broad access to information for its users, whatever is desired is always presented quickly so that its benefits are extraordinary. Therefore, insight into the impact of social media is a very important lesson material that needs to be socialized to the community, especially children and adolescents including Islamic boarding school students. However, in addition to having a positive impact, social media also has a negative impact on its users, including Islamic boarding school students as part of the digital generation. They are vulnerable to the negative impacts of social media such as addiction, behavioral changes, and security risks, increasingly becoming a concern in society, cyberbullying, liking uncivilized content, changes in social interaction and lifestyle and liking to apply new behaviors and habits. This can interfere with the learning process and character formation that is carried out in Islamic boarding schools. Therefore, there needs to be activities that can provide insight to Islamic boarding school students so that they also have digital awareness in using social media. Community service activities carried out at Tanwirul Qulub Islamic Boarding School and Darul Amin Islamic Boarding School are one of the activities that can provide benefits to students because with these activities, students can improve digital literacy, instill ethics and manners in using social media, increase creativity and technological skills, strengthen Islamic boarding schools as a place for comprehensive education, and encourage the use of social media for preaching.